Synthesis and Antimicrobial Activities of Some New Heterocyclic Compounds Based on 6-Chloropyridazine-3(2H)-thione - Nasser M. Abd El-Salam; Mohamed S. Mostafa; Gamal A. Ahmed; Othman Y. Alothman (Journal of Chemistry)
Three tricyclic ring system, pyridazino[6,1-b]quinazolin-10-ones, benzimidazolo-pyridazine thione, and 1,2,4-benzotriazino-pyridazinethione along with imidazo-[1,2-b]-pyridazinethione, 1,2,4-triazolo[4,3-b]pyridazine-thione derivatives were synthesized starting from 6-chloropyridazin3-(2H)-thione. Some disulfide and sulfide derivatives were also prepared. The antimicrobial activity of the synthesized compounds was tested. Some of these compounds possess a highly response against gram-positive and gram-negative bacteria as well as fungi.